Overcoming Legal Uncertainty for Justice Effectiveness Improvement - BOLOVNEV, M. A.; REKHTINA, I. V.; AKSENOVA, G. N.; MANKOVSKY, I. Yu.; SOKOLOV, A. S. (International Journal of Psychosocial Rehabilitation, 2020)
The article examines the impact of legal certainty of civil procedural legislation and the practice of its application on the appropriate conditions creation for the justice effective implementation. It is emphasized that the lack of legal certainty, namely, its opposite - legal ‘uncertainty’, creates both legislative conflicts, and, even more significant, law enforcement problems that significantly reduce the availability of justice for persons in need of judicial protection. Courts heterogeneously use established procedural rules, applying a formalistic approach, jeopardizing the issuance of a lawful and justified judicial act. In order to overcome the state of legal uncertainty and, as a result, increase the efficiency of legal proceedings, it is necessary to use such legal techniques that do not entail the appearance of casuistic legal norms. The model of the most general norms can be applied to any emerging procedural situation, taking into account the systemic and targeted methods of interpretation. Such an approach of building a legislation system, coupled with the subsequent application of norms based on internal conviction and judicial discretion that will ensure the unity of judicial practice.